The rebozo technique in the care of women in the pregnancy-puerperal cycle: an integrative review (Research, Society and Development, 2020)
Introduction: The gestational period is characterized by several hormonal changes, structures and psychosocial nature, providing the woman with a stage of preparation for the arrival of the baby. However, these changes often cause musculoskeletal discomfort due to postural changes mainly, among the main complaints is low back pain. Thus, there are approaches that are used to improve the quality and life of these pregnant women. One of these techniques is rebozo, a therapy that is effective and not widely used. Objective: to identify the effectiveness of the rebozo technique in assisting pregnant women. Methodology: This is an integrative literature review with a descriptive and qualitative approach, carried out by means of scientific articles that were related to the objective of the study, using the following databases and scientific platform, respectively: VHL, PubMED and periodical portal. Results and Discussions: the rebozo technique is a safe, effective, but little explored approach that promotes free movement, relaxation, pain reduction, relaxation and massage, and can be used during pregnancy, both in the pre-delivery and during labor, as well as postpartum. Conclusion: It was observed that this technique has great potential in the treatment and control of pain and discomfort from the gestational period, working strongly in the humanization of obstetric care.